For this exercise, I need to prove that the following sum

$\sum\limits_{i=0}^{n} \dfrac{(-1)^{n-i}(k+i)!}{(n-i)!(i!)^2}$

is equal to zero for $k = 0,1,...,n-1$ and one when $k=n$.

I already tried to solve this for some small values of $n$ to get an understanding of how I can prove this but I have absolutely no clue.


Starting from

$$\sum_{q=0}^n (-1)^{n-q} \frac{(k+q)!}{(n-q)! \times q!^2}$$

we find

$$k!\sum_{q=0}^n (-1)^{n-q} {k+q\choose q} \frac{1}{(n-q)! \times q!} \\ = \frac{k!}{n!} \sum_{q=0}^n (-1)^{n-q} {k+q\choose q} {n\choose q} \\ = \frac{k!}{n!} \sum_{q=0}^n (-1)^{n-q} {k+q\choose q} [z^{n-q}] (1+z)^n \\ = \frac{k!}{n!} [z^n] (1+z)^n \sum_{q=0}^n (-1)^{n-q} {k+q\choose q} z^q \\ = \frac{k!}{n!} (-1)^n [z^n] (1+z)^n \sum_{q\ge 0} (-1)^{q} {k+q\choose q} z^q \\ = \frac{k!}{n!} (-1)^n [z^n] (1+z)^n \frac{1}{(1+z)^{k+1}} \\ = \frac{k!}{n!} (-1)^n [z^n] (1+z)^{n-k-1} .$$

Now for $0\le k\le n-1$ this is clearly zero and for $k=n$ it evaluates to

$$(-1)^n [z^n] \frac{1}{1+z} = (-1)^{2n} = 1.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.